801 Obstructive Sleep Apnea Symptoms Predict Cognitive Function Following Mild Traumatic Brain Injury. (3rd May 2021) - Le, Andrew; Dailey, Natalie; Grandner, Michael; Killgore, William
Abstract: Introduction: Sleep disturbances are commonly reported following mild traumatic brain injury (mTBI). Specifically, one of these disturbances is obstructive sleep apnea (OSA), which involves repeated episodes of reduced upper-airway flow during sleep. When compared to the general population, OSA is reported at a much higher rate among the mTBI population. However, little research has investigated the relationship between OSA and cognitive performance among the mTBI population. We predicted that in those who suffered a mTBI, symptoms of sleep apnea would be predictive lower cognitive processing. Methods: We collected data from 37 healthy controls (Mean age = 24.3 □ 5.8) and 145 participants with mTBI (Mean age = 24.3 □ 6.8), ranging from 2 weeks to 12 months post-injury. Participants completed the Pittsburg Sleep Quality Index (PSQI) including questions indicative of OSA, such as "cannot breathe comfortably" and "cough or snore loudly" during sleep. We calculated the PSQI Sleep Disturbance (PSQI-SD) composite score, which ranged from 0 to 2. Participants completed the Automated Neuropsychological Assessment Metrics (ANAM4), a novel computer-based assessment, to measure reaction time (RT). Results: When comparing the percentage of participants in each group endorsing sleep disturbances on the PSQI-SD, we found a significant difference in the proportion of individuals scoring a 2 on PSQI-SD between the groups (□2(2) = 13.55, p = .001). In healthy controls, 8% scored 0, 89% scored 1, and 3% scored 2 on the PSQI-SD. In contrast, following mTBI, 1.4% scored 0, 72.4% scored 1, and 26.2% scored 2 on the PSQI-SD. Furthermore, PSQI-SD significantly predicted RT (□ = .18, p = .03) in the mTBI group, a relationship not observed in the control group (□ = .30, p = .07). Conclusion: mTBI increases the incidence of sleep disturbances and symptoms related to OSA. Furthermore, sleep disturbances and OSA-related symptoms were predictive of cognitive performance in individuals who sustained a mTBI, but not healthy controls. Increases in PSQI-SD scores were associated with increased RT, indicating greater deficits in cognitive function, specifically reaction time. These data provide evidence that higher severity in respiratory symptoms relating to sleep apnea hinders cognitive processing, particularly for individuals who have suffered a mTBI. Support (if any):